1999
DOI: 10.1111/j.1651-2227.1999.tb01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural effects in female rats of postnatal exposure to sub‐toxic doses of polychlorinated biphenyl congener 153

Abstract: Holene E, Nafstad I, Skaare JU, Krogh H, Sagvolden T. Behavioural effects in female rats of postnatal exposure to sub-toxic doses of polychlorinated biphenyl congener 153. Acta Paediatr 1999; Suppl 429: 55-63. Stockholm. ISSN 0803-5326 Polychlorinated biphenyls (PCBs) are widespread environmental contaminants that are also present in human tissues and breast milk. Behavioural disturbances have been reported in both children and animals exposed perinatally to PCBs. The present study assessed the behavioural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…In these rat studies, PCBs also produced increased motor activity, which was observed in young but not aging mice in our previous study (Rice et al 2007). Other studies in rats found no effect on FI performance (Holene et al 1999; Taylor et al 2002). …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In these rat studies, PCBs also produced increased motor activity, which was observed in young but not aging mice in our previous study (Rice et al 2007). Other studies in rats found no effect on FI performance (Holene et al 1999; Taylor et al 2002). …”
Section: Discussionmentioning
confidence: 64%
“…Although FR and FI are both simple operant schedules, apparently they have not been examined after developmental PBDE exposure. Developmental PCB exposure produced changes in FI performance in some studies (Holene et al 1998; Lilienthal et al 1990; Rice 1997) but not others (Holene et al 1999; Rice and Hayward; 1998; Taylor et al 2002). Differences may have been due to different congener mixtures, species differences, sex-specific effects, or other differences in dosing and testing protocol.…”
mentioning
confidence: 86%
“…A similar type of response pattern (shorter IRTs and more responses made per reinforcer earned) has been seen subsequent to developmental PCB exposure in rats (Holene et al 1999), monkeys (Rice 1998), and children (Stewart et al 2006) during differential reinforcement of low rates of response (DRL) operant tasks. DRL tasks measure timing and inhibitory control and differ from FI tasks in that the interval clock resets if a response is made before the end of the interval.…”
Section: Introductionmentioning
confidence: 62%
“…Not all studies report negative effects of developmental PCB exposure on FI (Holene et al 1999; Rice and Hayward 1998; Taylor et al 2002), DRL (Rice and Hayward 1998; Sable et al 2006), or extinction (Holene et al 1999) tasks. These divergent results underscore the potential influence of factors such as dose, timing of exposure, sex of the animal and chlorine substitution pattern of the PCB congener or mixture on task performance.…”
Section: Introductionmentioning
confidence: 99%
“…Lactational exposure of rats to PCB-153 produced increased responding during FI training and extinction in male rats (Holene et al 1998) but not in female rats (Holene et al 1999). In a separate study, juvenile male rats exposed to either PCB-contaminated fish or Aroclor 1248 concentrations equivalent to those in the fish (Berger et al 2001) showed increased lever pressing and bursts of responding on an FI task.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 96%